O TRABALHO DAS PROSTITUTAS QUE RESIDEM EM CASAS NOTURNAS: UMA PERSPECTIVA PSICODINÂMICA. - Ribeiro, Nívia Chaves (2010)
A case study of descriptive and exploratory was conducted aiming to investigate the meanings attributed to work and the experience of prostitutes living in nightclubs in relation to their work in the light of the psychodynamics of work. The specific objectives of the research were: to investigate the meanings that the prostitutes who live in nightclubs attach to their work, investigate and analyze the organization of work of prostitutes who live in nightclubs, investigate and analyze the working conditions of prostitutes living in nightclubs, investigate and analyze the working relations of prostitutes living in nightclubs; investigate aspects that trigger experiences of pleasure and suffering in prostitutes who live in nightclubs, raise and describe the coping strategies, individual and collective, that prostitutes residing in nightclubs develop to deal with suffering at their work. The participants were chosen considering the inclusion criteria as: female, over 18 year olds, profession as prostitutes who live and work in a nightclub. Obeying these criteria, 15 women were interviewed between 18 and 35 years, with educational level ranging from completed elementary school and incomplete college. To collect the data the documentary analysis techniques and individuals semi-structured interviews were used and for data processing the technique of Graphical Analysis of the Discourse. During data analysis it was revealed that the company studied, like any other, has positive and negative aspects in the management of the organization and subjectivity of the worker. As to the organization of work this is presented in a rigid way, making it impossible to balance the needs of the participants with the demands of work, highlighting the enforcing of a rhythm that neglects the welfare of workers. The time available for the activities of rest and relaxation are also not enough for them. The speech of the interviewees shows that the organization offers good food, but is weak in accommodation and in its physical structure, including reports of compromised health problems due to noise, smoke and drink. In working relations the process is satisfactory with colleagues and customers, however conflicting with management, triggering factor of suffering experiences once the control and hierarchical imposition prevails on the workers. Nowadays the working relations guide a demanding human being who seeks for his wellbeing to better share the social welfare as an actor and not just a spectator. For the prostitutes, the experiences of pleasure sustained by the recognition between them some customers, the possibility of fulfilling the dream of "out of this life, to help the family, and to go back to school, made up for the experiences of suffering coming from homesickness , tiredness and natural wear of "evenings", and society discrimination.